Macroporous MoS2/carbon hybrid film with superior ion/electron conductivity for superhigh areal capacity Li-ion batteries. (2nd November 2019) - Zhang, Haoxuan; Liu, Yu; Jiang, Hao; Deng, Zongnan; Liu, Honglai; Li, Chunzhong
Graphical abstract: Highlights: An entirely new insight into constructing superhigh areal-specific-capacity LIBs. The MoS2 /C hybrids film facilitates superior ion/electron transport capability. A four-film stacked electrode delivers an areal specific capacity of 7.21 mA h cm −2 . A flexible all-solid-state full cell is assembled with great Li + storage capability. Abstract: The development of flexible lithium-ion batteries (LIBs) with very high areal capacity becomes extremely important in achieving precision medicine due to the limited area of the involved LIB devices. However, the improvement of areal capacity using well-known conventional strategies unavoidably engenders serious polarization and gravimetric specific capacity fading. Herein, we report an entirely new insight into constructing superhigh areal-specific-capacity LIBs by designing an electron/ion dual-conductive macroporous MoS2 /C hybrid film. A four-film stacked electrode even with a high mass loading of ∼12.0 mg cm −2 can deliver an unprecedented high areal specific capacity of 7.21 mA h cm −2, almost double that of best material reported to date (4 mA h cm −2 ). Such film electrode unexpectedly shows a positive linear increase of areal specific capacity versus layer number, but no gravimetric capacity (high value of ∼600 mA h g −1 ) change. The electrode kinetics studies reveal that such superhigh areal-specific-capacity lithium storage is mainly attributed to excellent ion transport (10 −8 –10 −9  cm 2  s −1 ) and electron transfer (21.3 S cm −1 ) of three-dimensional macroporous MoS2 /C hybrid film. This work demonstrates a new concept of dual-conductive film electrode for the development and application of LIBs with tailorable areal specific capacity.